2020
DOI: 10.1002/rmb2.12317
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of microdissection testicular sperm extraction and intracytoplasmic sperm injection in Japanese men with Y chromosome microdeletions

Abstract: Purpose We investigated the clinical results of Japanese men with Y chromosome microdeletions. Methods This study retrospectively examined 2163 azoospermic or severe oligozoospermic patients. We investigated the frequency of azoospermia factor (AZF) deletions and sperm retrieval rate (SRR) by microTESE in patients with these deletions, then analyzed the ICSI outcomes. Results Azoospermia factor deletions were found in 201 patients. SRR was significantly higher than that of the control group (74.0% vs 20.4%, P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The AZFc microdeletion group exhibited the highest positive SSR outcome with 41.95%, while the KS group had a success rate of 38.63%. The higher SSR in AZFc microdeletion patients is consistent with previous studies and may be due to the varying histopathology patterns attributed to this microdeletion as well as a number of foci for spermatogenesis within the testis (Hopps et al, 2003;Sabbaghian et al, 2018;Yamaguchi et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The AZFc microdeletion group exhibited the highest positive SSR outcome with 41.95%, while the KS group had a success rate of 38.63%. The higher SSR in AZFc microdeletion patients is consistent with previous studies and may be due to the varying histopathology patterns attributed to this microdeletion as well as a number of foci for spermatogenesis within the testis (Hopps et al, 2003;Sabbaghian et al, 2018;Yamaguchi et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…Quality assessment of the included studies revealed the majority of studies (n = 37; 69.81%) to be of fair quality scoring a total of 6 stars, while the remaining 16 (30.19%) studies were considered of high quality (8 studies scoring 9 stars (Bakircioglu et al, 2011;Chehrazi et al, 2017;Choi et al, 2013;Ishikawa et al, 2009;Plotton et al, 2015;Tsujimura et al, 2004;Yamaguchi et al, 2020;Zhang et al, 2021) and 8 studies scoring 7 stars (Arafa et al, 2018;Chen et al, 2019;Huang et al, 2020;Iwatsuki et al, 2017;Klami et al, 2018;Kleiman et al, 2016;Ko et al, 2016;Takeda et al, 2017).…”
Section: Search Results and Characteristics Of Studiesmentioning
confidence: 99%
“…As a result, patients with azoospermic AZFc deletion can undergo ICSI with either testicular or ejaculated sperm with the help of assisted reproductive technology (ART). Some studies (2,(9)(10)(11)(12)(13) have reported that AZFc microdeletions do not affect the clinical outcome because patients with both azoospermia and severe oligozoospermia AZFc deletions exhibited similar outcomes with that of patients with a normal Y chromosome. It has been reported recently (14) that patients with AZFc deletion showed unsatisfactory outcomes compared with patients with other nonobstructive azoospermia (NOA) in a small sample size (n ¼ 91), but they did not investigate the reason for this poor outcome.…”
mentioning
confidence: 99%
“…Compared to ICSI using microTESE and ejaculatory sperm, the outcome of later sperm performed better [13,14,22]. In this study, our results show that PGT-A can signi cantly improve clinical outcomes after ICSI with ejaculated sperm in AZFc patients.…”
Section: Discussionmentioning
confidence: 53%